Qualitative and practical analysis of chemical residues as an indicator in the preparation and consumption of food in southern Central America: contributions from experimental archeology: Aportes desde la arqueología experimental - Núñez-Cortés, Yajaira (2022)
Controlled enrichment experiments contribute to the interpretation of the archaeological record to the extent that they expand the knowledge about the chemical footprints left by specific substances. In this paper I present the results of experimentation with foods reported archaeologically in southern Central America to enrich modern ceramics, to which I tested for phosphates, carbonates, hydrogen potential (pH), carbohydrates, protein residues and fatty acids. The experimental groups involved: 1) enrichment by pouring broths of fish, clams, beans, manioc, peach palm and corn chicha for four weeks, and 2) differential enrichment by boiling fish, clams, manioc and beans, roasting corn and cocoa, and corn fermentation to produce chicha. The results indicate differentiations between the substances used and the types of experiments, which will be affected by post-depositional processes.